Exploring the Interplay of Professionalism and Organizational Commitment in Enhancing Human Resource Productivity: Evidence from a Military Hospital - Wahyuddin Bagenda; Mira Veranita; Rinawati (International Journal Administration, Business & Organization, 2026)
This study examines the roles of professionalism and organizational commitment as predictors of human resource (HR) productivity in a military hospital (Hospital X) in the Special Region of Yogyakarta, Indonesia. A descriptive qualitative single case study was employed. Data were collected through semi-structured interviews with ten purposively selected informants representing multiple organizational levels, supported by participant observation and document review. Data were analyzed using Braun and Clarke's (2006) six-phase thematic analysis with source and method triangulation. Data saturation was achieved at the eighth informant. The findings reveal that HR professionalism was generally adequate but constrained by cross-assignment practices involving 60% of nursing staff, nurse-to-patient ratios exceeding recommended standards (1:10 versus 1:4–1:6), and administrative tasks consuming approximately 40% of nurses' working time. Affective commitment emerged as the strongest dimension of organizational commitment, while continuance commitment remained the weakest, particularly among younger and civilian personnel. The study also identified a synergistic interaction between professionalism and organizational commitment in enhancing HR productivity, rather than a simple additive effect. Furthermore, military-specific contextual factors, including command hierarchy, dual workforce composition, and dual operational demands, moderated these relationships. Based on these findings, the study proposes a conceptual model in which affective commitment mediates the relationship between professionalism and HR productivity, while hierarchical structure and role duality function as contextual moderators. These findings extend conventional human resource management models and provide practical implications for developing integrated managerial strategies to improve workforce productivity in military healthcare organizations.